Fractional descriptor continuous-time linear systems described by the Caputo-Fabrizio derivative - Kaczorek, Tadeusz (1932- ); Borawski, Kamil (Zielona Góra: Uniwersytet Zielonogórski)
The Weierstrass-Kronecker theorem on the decomposition of the regular pencil is extended to fractional descriptor continuous-time linear systems described by the Caputo-Fabrizio derivative. A method for computing solutions of continuous-time systems is presented. Necessary and sufficient conditions for the positivity and stability of these systems are established. The discussion is illustrated with a numerical example.
Keywords: fractional systems; descriptor systems; continuous-time; linear systems; Caputo-Fabrizio derivative